ANALISIS KELAYAKAN USAHA DARI ASPEK EKONOMI DAN KEUANGAN PADA USAHA KERUPUK TAPIOKA DIKECAMATAN KUALA PESISIR KABUPATEN NAGAN RAYA - Leli Putri Ansari; Ivon Jalil; Yayuk Eko Wahyuningsih (Universitas Teuku Umar, 2019)
This business of tapioca crackers is one type of micro, small, and medium enterprises (MSMES) that develop in the district of Kuala coastal Nagan Raya Regency. Cracker Crackers is a snack that is usually eaten along with rice as a complement to other side dishes. In general, tapioca crackers made from flour dough tapioca mixed flavourings such as shrimp or ikanditsprouts with other kitchen spices such as salt, garlic, and coriander. The research aims to analyse the feasibility of business development from the economic and financial aspects of tapioca crackers in the district of Kuala coastal Nagan Raya Regency with a population and samples as many as 15 tapioca crackers. Sampling techniques using purposive sampling. The data used is the primary data sourced from the results of a live interview with the business of tapioca crackers and secondary data obtained from the Central Statistical Agency (BPS) Nagan Raya District. The research methods in this study use qualitative, comparative descriptive techniques and data analysis models using the business feasibility analysis of the economic and financial aspects of the analysis tools used include profit analysis (Profit), Benefit Cost Ratio (B/R) analysis, point analysis Break Event Point, analysis of business impact on the community economy. The results showed that from 15 units obtained profit (Profit) on average of Rp 13,404,400 where the highest profit (Profit) obtained by the business of tapioca crackers Smooth crackers Rp 18.400.000 and profit (profit) lowest obtained by the effort of Tapioca sun crackers amounting to Rp 8,210,000 per month. Benefit Cost Ratio (B/R) > 1, Break Event Point which obtained in average unit of 6,920 kilogram in average of rupiah is about Rp 23,000 per kilogram. So it can be deduced 15 business units of tapioca crackers are worthy to continue to be developed. Keywords: business feasibility analysis, economic aspects, financial aspects